Effect of NR/NBR ratio on mechanical properties and crosslink concentration of NR/NBR blend latex film - M Salih, Norzahida; Aisyah Jarkasi, Siti; Samsuri, Azemi; Zaharah Engku Zawii, Engku; Ibrahim, Norazura; Kamarun, Dzaraini (International Journal of Engineering and Technology, 2018)
It is a common practice to blend two elastomers of different properties with a view to combine the best properties of each in terms of its technical and economic values. Nitrile rubber (NBR) is blended with natural rubber (NR) to meet the requirements for very good oil resistance as well as high mechanical strength. The former is a polar rubber and provides very good oil resistance, while the latter is non-polar and provides excellent mechanical properties. Numerous works on rubber blends that have been reported are based on dry rubber. On the contrary, the work on rubber blends base on latex received less attention than the dry rubber. This paper describes the work on NR latex and NBR latex blends. NR and NBR were blended at several ratios incorporating NBR up to 50% to study their effect on the mechanical properties and crosslink concentrations. The glass transition temperatures, Tg and the morphology of NR/NBR latex blends were determined to verify the compatibility of the blends.Â The results indicated that tensile strength (TS) showed a good linear relationship with loadings of NBR. The decreased in TS with decreased in NR content of the blends was associated with low crosslink concentrations in the rubber blends. Both elongation at break (EB) and tear energy are affected non-linearly by the presence of NBR indicating the incompatibility of the two rubber components.Â Â